Making the CAADP BR forward looking: A decision support tool for transforming African agrifood systems - Benin, Samuel (International Food Policy Research Institute, 2024)
This paper presents an Excel-based interactive decision-support tool that policymakers and development practitioners can use to evaluate policy options to achieve targeted outcomes of the Malabo Declaration at the country level. The tool is based on a partial equilibrium simulation model that allows the user to simulate different scenarios based on the desired level of change in one outcome or more. For each scenario that is created, the simulated results provide information on the level of change required in each of the policies included in the model, the level of change in the other outcomes included in the model, and the allocation of the resources provided, including reallocation of some of the existing resources. A prototype of the tool that is developed using the fourth biennial review (BR) data on Ghana, which has some quality issues, is presented to demonstrate the potential features and utility of the tool.